Analysis of the effectiveness of active paper use by adding garlic extract in inhibiting bacterial growth. Issue 1 (October 2020) - Hidayat, S H; Syarifuddin, A; Dirpan, A
Abstract: Active paper is a component with antibacterial properties, often used as a microorganism resistance regulator, alongside ensure quality maintenance, and provide safety for packaged products. The purpose of this study, therefore, is to evaluate the effectiveness of active paper added with garlic extract in inhibiting bacterial growth. This involved the addition of 20% garlic extract, 30% tapioca starch (w / w), 100 mL of 1% acetic acid and chitosan powder into whatman paper pulp, followed by testing on Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa bacteria. The results showed a zone of bacterial inhibition with respective diameter of 3.68 mm, 3.98 mm and 1.98. However, active paper alone does not possess these inhibitory properties.